Perspektif Al-Qur’an tentang Nilai Moderasi Beragama untuk Menciptakan Persatuan Indonesia - Alfaini, Sania (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2021)
From an Islamic perspective, morality or morals have a high position. Thus the high The differences that exist in the Indonesian nation makes its people appreciate and respect all kinds of diversity, one of them in religion. The attitude that can be taken by a Muslim to balance aspects of nationality and religion is to moderate religion. The research method used is descriptive qualitative with the collection of theoretical triangulation of various literature studies and domain analysis between various concepts.Religious moderation is taken from the perspective of the Qur'an with several interpretation references. It can be concluded that religious moderation in its implications in accordance with the teachings of the guidelines of Muslims, namely the Qur'an. Abstrak Perbedaan yang ada pada bangsa Indonesia menjadikan rakyatnya menghargai dan menghormati segala macam keragamannya, salahsatunya dalam beragama. Sikap yang dapat diambil oleh seorang muslim untuk menyeimbangkan aspek kebangsaan dan keagamaan adalah dengan bermoderasi agama. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pengumpulan triangulasi teori dari berbagai studi literatur dan analisis domain antar berbagai konsepnya. Moderasi beragama diambil dari perspektif Al-Qur’an dengan beberapa rujukan tafsiran. Dapat disimpulkan bahwa moderasi beragama dalam implikasinya sesuai dengan ajaran pedoman umat Islam, yakni Al-Qur’an.